METHODOLOGICAL PRINCIPLES OF STRUCTURING CONTENTS OF SUBJECTS OF THE HUMANITARIAN CYCLE IN THE PROCESS OF PROFESSIONAL TRAINING OF STUDENTS OF PEDAGOGICAL HIGHER EDUCATION INSTITUTIONS - Ustinova, В. О. (Pedagogy of Higher and Secondary Education, 2022)
This article determines methodological basis of Art courses contents in the process of teaching students in pedagogical higher education establishments.